GAP analysis of consumer’s expectation versus their perception of Sun Home Energy Ltd.’s service - Talukder, Md. Mahfuzur Rahman (BRAC University, 2019)
This internship report is submitted in partial fulfillment of the requirements for the degree of Masters of Business Administration, 2018.